Analisis Akses Pembiayaan Formal Petani Cabai Merah Di Kabupaten Garut - Agum Restu Alam; Eliana Wulandari; Fanny Widadie (Universitas Garut, 2025)
Access to formal financing is key to the sustainability of red chili farming in the Garut District due to price fluctuations and high capital requirements. This study aims to assess the level of access of red chili farmers to formal financing and identify its supporting factors. The study was conducted in Kecamatan Cikajang from February to May 2025 with a quantitative approach using a survey of 108 randomly selected farmers from five production center villages. Data were analyzed with descriptive statistics to explore the relationship between farmer characteristics (age, education, farming experience, land size) and access to formal financing. The results showed that only 11.1% of farmers successfully accessed formal credit, while 88.9% did not access formal financing. Frequency analysis and significance tests revealed no significant relationship between demographic variables and access to finance, with the main barriers being complex procedures, low financial literacy, and weak farmer institutions. The study recommends increasing financial literacy programs, simplifying credit procedures, and strengthening farmer group institutions to expand financial inclusion in the horticulture sector.Keywords: Access to Finance, Red Chili Farming, Garut, Formal Financing